Analysis of Students' Learning Interest During The Covid-19 Pandemic - Putri Kiantan (International Journal of Learning and Instruction (IJLI), 2021)
Abstract This study aims to describe learning interest in social science subjects during the Covid-19 pandemic. The research method used was descriptive with a qualitative approach. The subjects of this study were eighth grade of G students of SMPN 15 Pontianak. The research indicators were the students' feelings, attention, interest, and involvement. Data were collected using observation, interviews, and documentation techniques. Data collection tools were in the form of observation guidelines, interview guides, and documentation tools. The informants in this study were students of eighth grade and social science teachers. The study showed that (1) during the learning process, students felt happy with the subjects; therefore, the learning atmosphere became fun. (2) Their attention on the lesson was quite good due to the lack of participation during learning via Google Meet. There were only some students who paid attention and took notes on the material. However, it was seen that students prepared the textbooks well. (3) The learners' interest in the social sciences subjects was good, seen from their enthusiasm in participating in an online class. (4) The involvement of students in social science learning was also quite good, seen from the activeness of students actively asking questions and doing assignments. Keywords: Covid-19 Pandemic, Learning Interest, Qualitative